Swearing-in Ceremony for New Attorneys Held at Wine Press Room at Selland Arena - Watkins, Howard::::::::: (1989)
Judy Soley seated; L to r: ?,?, Jim Petrucelli, Mary Louise Frampton, Scott Williams and